Perancangan Sound Energy Harvesting Berbasis Material Piezoelektrik untuk Memanfaatkan Kebisingan di Sepanjang Ruas Pantai Losari menuju Losari sebagai Ruang Publik Hemat Energi - Iqbal Ramli; Irfan Irfan (Hasanuddin University, 2017)
Utilization of alternative energy sources is still very minimal in the area of Losari Beach. Noise from visitors can be used as an alternative energy source in Losari Beach area. Sound saves potential energy that can be generated. In the process of utilization, piezoelectric material will be given input from the noise of the visitors of Losari Beach beach. This research will analyze the electrical energy generated (power on LED lamp) from piezoelectric material to various condition in Losari Beach area. The results of the study found the amount of output generated when the piezoelectric material is not coupled in series is 0.7 volts, while at the time strung in series reaches 1.9 volts. Makassar city government support, is expected in implementing the results of this study.Keywords: Losari Beach, sound, energy harvesting, piezoelectric